2015
DOI: 10.4209/aaqr.2014.01.0014
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Measurements of Ultrafine Particles and Associated Air Pollutants in a Densely Populated Area of Seoul, Korea

Abstract: Spatial distributions of ultrafine particles (UFPs; 6 < D p < 560 nm) and related gaseous and particulate pollutants were estimated from on-road measurements undertaken on busy roadways of Seoul, Korea, using a mobile laboratory (ML). The objectives of the study were to determine the spatial variations in UFP size distributions and concentrations of associated gaseous and particulate pollutants and to observe the relationships of UFP number concentrations with other pollutants on roadways in an urban area in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The large differences in the PN 1-0.01 concentrations of submicron aerosols between on-road and off-road measurements in this remote area were consistent with previous near-road aerosol measurements [14]. The differences are thought to be due to the dispersion and dilution while aerosols are transported away from the road, where car emissions are concentrated the most, as illustrated by mobile laboratory measurements [4,6,13].…”
Section: On-road Conditions In a Remote Areasupporting
confidence: 86%
See 2 more Smart Citations
“…The large differences in the PN 1-0.01 concentrations of submicron aerosols between on-road and off-road measurements in this remote area were consistent with previous near-road aerosol measurements [14]. The differences are thought to be due to the dispersion and dilution while aerosols are transported away from the road, where car emissions are concentrated the most, as illustrated by mobile laboratory measurements [4,6,13].…”
Section: On-road Conditions In a Remote Areasupporting
confidence: 86%
“…Usually, the traffic activity is characterized by two main rush hours (morning and afternoon) on workdays [53][54][55][56][57]. Such diurnal patterns have not only been reported in Jordan, but also in many other urban environments worldwide [35,53,[58][59][60][61][62][63][64][65][66]; differences might be due to the variations related to traffic activities and vehicle type mix [6,16,18,25]. For instance, Rahman et al [53] reported a workday PN 1-0.01 diurnal pattern at an urban site in Brisbane (Australia); the concentrations were close to 9 × 10 3 cm −3 during the morning and afternoon rush hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, numerous studies used the Fast Mobility Particle Sizer (FMPS) (Westerdahl et al, 2009;Sabaliauskas et al, 2012;Betha et al, 2014;Kim et al, 2015) or the Scanning Mobility Particle Sizer (SMPS) coupled with the condensation particle counter (CPC) (Chen et al, 2010a;Breitner et al, 2011;Jayaratne et al, 2011;Wang et al, 2011;Xu et al, 2011;Gao et al, 2012;Young et al, 2012;Cheung et al, 2013;Young et al, 2013;Cheng et al, 2014) to investigate the number concentrations of UFPs. Most of the researches have shown that both local rush hour traffic emission and new particle formation (NPF) play key roles in the diurnal variation of UFPs concentrations, in which two concentration peaks in the morning and evening could be attributed to traffic emission, while one peak in the afternoon is due to NPF (Young et al, 2012;Cheung et al, 2013;Young et al, 2013;Betha et al, 2014;Nikolova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their outdoor sources include steel plants, coal fired power plants, vehicle emissions, municipal solid waste incinerators, biomass burning, whereas indoor sources can be from building and furnishing materials, heating and cooking facilities, cigarette smoke, incense burning, and etc. (Madany et al, 1994, Li et al, 2005Fang et al, 2004;Kume et al, 2007;Amodio et al, 2013;Da et al, 2013;Park et al, 2013;Yang et al, 2013;Li et al, 2014;Kim et al, 2015). The presence of PAHs in indoor dust, in particular the carcinogenic and mutagenic PAHs with 4-7 rings, may pose serious threats to human health.…”
Section: Introductionmentioning
confidence: 99%